2023
DOI: 10.1212/wnl.0000000000207422
|View full text |Cite
|
Sign up to set email alerts
|

Association of Alternative Anticoagulation Strategies and Outcomes in Patients With Ischemic Stroke While Taking a Direct Oral Anticoagulant

Abstract: Background and Objectives:Ischemic stroke despite direct oral anticoagulant (DOAC) is increasingly common and portends high risk of subsequent ischemic stroke. Efficacy and safety of antithrombotic regimens following the condition are unclear. We aimed to compare the outcomes of patients with ischemic stroke despite DOAC with and without an alternative antithrombotic regimen, and determine the risk factors of recurrent ischemic stroke while on anticoagulation.Methods:In a population-based, propensity-score wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 40 publications
1
16
1
Order By: Relevance
“…We sincerely thank Wolfe et al for the comments. The low rate of large artery atherosclerotic disease (LAD) in our atrial fibrillation (AF) cohort 1 echoed our other study that among ischemic strokes, the proportion of intracranial atherosclerotic disease declined from 23.3% to 8.8% from 2004 to 2018 in Hong Kong. 2 This difference may explain the disparity in LAD rates because the cohort of minor strokes/TIA quoted was recruited from 2011 to 2015.…”
supporting
confidence: 84%
“…We sincerely thank Wolfe et al for the comments. The low rate of large artery atherosclerotic disease (LAD) in our atrial fibrillation (AF) cohort 1 echoed our other study that among ischemic strokes, the proportion of intracranial atherosclerotic disease declined from 23.3% to 8.8% from 2004 to 2018 in Hong Kong. 2 This difference may explain the disparity in LAD rates because the cohort of minor strokes/TIA quoted was recruited from 2011 to 2015.…”
supporting
confidence: 84%
“… 18 Regarding safety, all investigations showed that changing or retaining prestroke DOAC resulted in a comparable ICH risk. However, our study reported a relatively higher hazard ratio for ICH than the other 2 studies (ie, 1.49 versus 1.06 for Hong Kong and 1.03 for Taiwanese studies), 17 , 18 implying that a large‐scale investigation will be required for validation.…”
Section: Discussioncontrasting
confidence: 61%
“…A Hong Kong study demonstrated that changing the prestroke DOAC to a different DOAC or warfarin increased the risk of recurrent IS. 17 Results from another Taiwanese study showed comparable recurrent stroke risk in patients who changed from a prestroke DOAC to another DOAC but increased IS risk in patients who changed from DOAC to warfarin. 18 Regarding safety, all investigations showed that changing or retaining prestroke DOAC resulted in a comparable ICH risk.…”
Section: Discussionmentioning
confidence: 97%
“…Emerging evidence from prospective observational cohorts [12,15,16] and post hoc analysis of the pivotal RCT comparing DOACs with VKA in patients with AF [17] found patients with breakthrough strokes despite OAC to be at increased risk of further recurrence constituting a highly vulnerable patient population. The optimal prevention strategy to further reduce recurrence risk in such patients is still unknown [15,18,19]. Breakthrough strokes may be caused by competing, non-AF-related mechanisms (i.e., large or small vessel disease), which accounts for The latest European and American guidelines for management of AF recommend DOAC in preference to VKA for stroke prevention in selected AF patients (excluding patients with mechanical heart valves or moderate-to-severe mitral stenosis) with increased stroke risk [4,22].…”
Section: Introductionmentioning
confidence: 99%